FOREIGN AND DOMESTIC CLUSTER DEVELOPMENT EXPERIENCE - O. D. Gaisha (Вестник университета)
The article considers such integration of subjects as a cluster, which represents a form of association of the interconnected companies in a certain territory, including scientific and technical and production enterprises, universities and research centers. The foreign experience of cluster development and in parallel the formation and functioning of domestic clusters has been analyzed. Based on the research, the directions for improving the domestic cluster policy have been proposed. The research used the methods of bibliographic and logical analysis.